List of the Homoptera Coccoidea of North-Eastern Italian regions (Bollettino di zoologia agraria e bachicoltura, 2024)
A list ofthe species known to live in North-Eastern ltalian regions (Venetia, Friuli-Venetia Julia, Trentino), is reported. This list includes information compiled up December 31, 1993 and records 147 species distributed in 11 families.
Keywords: Homoptera Coccoidea; regional list